Chitosan Feasibility to Retain Retinal Stem Cell Phenotype and Slow Proliferation for Retinal Transplantation. (2nd February 2014) - Srivastava, Girish K.; Rodriguez-Crespo, David; Singh, Amar K.; Casado-Coterillo, Clara; Fernandez-Bueno, Ivan; Garcia-Gutierrez, Maria T.; Coronas, Joaquin; Pastor, J. Carlos
Abstract : Retinal stem cells (RSCs) are promising in cell replacement strategies for retinal diseases. RSCs can migrate, differentiate, and integrate into retina. However, RSCs transplantation needs an adequate support; chitosan membrane (ChM) could be one, which can carry RSCs with high feasibility to support their integration into retina. RSCs were isolated, evaluated for phenotype, and subsequently grown on sterilized ChM and polystyrene surface for 8 hours, 1, 4, and 11 days for analysing cell adhesion, proliferation, viability, and phenotype. Isolated RSCs expressed GFAP, PKC, isolectin, recoverin, RPE65, PAX-6, cytokeratin 8/18, and nestin proteins. They adhered (28 ± 16%, 8 hours) and proliferated (40 ± 20 cells/field, day 1 and 244 ± 100 cells/field, day 4) significantly low ( P < 0.05 ) on ChM. However, they maintained similar viability (>95%) and phenotype (cytokeratin 8/18, PAX6, and nestin proteins expression, day 11) on both surfaces (ChM and polystyrene). RSCs did not express alpha-SMA protein on both surfaces. RSCs express proteins belonging to epithelial, glial, and neural cells, confirming that they need further stimulus to reach a final destination of differentiation that could be provided in in vivo condition. ChM does not alternate RSCs behaviour and therefore can be used as a cell carrier so that slow proliferating RSCs can migrate and integrate into retina.